BEYOND THE BUSINESS CASE: AN INTERSECTIONAL ANALYSIS OF DIVERSITY, EQUITY, AND INCLUSION INITIATIVES ON PSYCHOLOGICAL OWNERSHIP - Arwan Kasri; Ramon Zamora; Oktavianti (RADJA PUBLIKA, 2026)
Diversity, Equity, and Inclusion (DEI) initiatives have become increasingly important in contemporary organizations, yet their effectiveness is often evaluated through a business-case perspective emphasizing productivity, innovation, and financial performance. This study aims to move beyond such perspectives by examining the relationship between DEI initiatives and psychological ownership through an intersectional lens. Using a qualitative narrative literature review approach, relevant studies from organizational behavior, human resource management, diversity management, and social psychology were analyzed to identify key themes and theoretical insights. The findings indicate that DEI initiatives foster psychological ownership by enhancing employees’ perceptions of fairness, inclusion, belonging, recognition, and participation. The review further demonstrates that the impact of DEI initiatives varies across employees with different intersecting social identities, highlighting the importance of intersectionality in understanding workplace experiences. This study contributes to the literature by positioning psychological ownership as a critical employee-centered outcome and advocating for more inclusive and intersectionally informed DEI strategies.